2019
DOI: 10.1177/2168479018791136
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Assessment in Japan: A Pharmaceutical Industry Perspective

Abstract: Although the government decided to implement HTA for the pricing scheme in 2018, a shortage of experts and researchers remains a challenge. Findings suggest HTA should not be used solely to reduce pharmaceutical spending, as the impact by the HTA implementation will be temporary and discourage innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Across Sweden, Germany, France, the UK, and South Korea, for example, staffing of these authorities ranges from 125 to 2,121 individuals, with annual budgets ranging from 2.33 to 36.25 billion JPY, respectively 2 . Except for Chuikyo and C2H, Japan does not have a dedicated HTA authority, and there is concern among clinicians and industry that there is a need to strengthen HTA expertise among MHLW personnel 9,24 . A further potential concern is that lack of capacity to undertake HTAs could introduce delays to patient access to new treatment options in the future 24 .…”
Section: Capability and Infrastructurementioning
confidence: 99%
See 4 more Smart Citations
“…Across Sweden, Germany, France, the UK, and South Korea, for example, staffing of these authorities ranges from 125 to 2,121 individuals, with annual budgets ranging from 2.33 to 36.25 billion JPY, respectively 2 . Except for Chuikyo and C2H, Japan does not have a dedicated HTA authority, and there is concern among clinicians and industry that there is a need to strengthen HTA expertise among MHLW personnel 9,24 . A further potential concern is that lack of capacity to undertake HTAs could introduce delays to patient access to new treatment options in the future 24 .…”
Section: Capability and Infrastructurementioning
confidence: 99%
“…Except for Chuikyo and C2H, Japan does not have a dedicated HTA authority, and there is concern among clinicians and industry that there is a need to strengthen HTA expertise among MHLW personnel 9,24 . A further potential concern is that lack of capacity to undertake HTAs could introduce delays to patient access to new treatment options in the future 24 . A recent analysis of 569 oncology HTAs for drugs approved in Canada, Australia, France, Germany, and the UK showed that it takes a median of 214 days from regulatory approval to a reimbursement decision 25 .…”
Section: Capability and Infrastructurementioning
confidence: 99%
See 3 more Smart Citations